Inward and outward FDI in Lithuania and Estonia: Review of patterns in neighboring countries - Ginevičius, Romualdas; Tvaronavičiene, Manuela (Journal of Business Economics and Management, 2005)
The paper aims to trace how important state policies, cultural differences and neighborhood of developed countries are as driving forces attracting foreign capital inflows. Authors overview the inward and outward foreign direct investment (FDI) tendencies in Lithuania and Estonia, reveal similarities and differences of the neighbor countries. Authors distinguish and discuss a role of privatization policy in attracting foreign direct investments. The assumption about different inward FDI sources caused by different privatization strategies adopted by considered countries is to be elaborated. Another focus of presented paper is outward FDI structure in terms of capital origin, and differences of its in scale in two Baltic countries – Lithuania and Estonia. Phenomenon of Scandinavian FDI channeling through Estonia is to be traced and interpreted. First published online: 14 Oct 2010